Introduction to time series analysis and forecasting - Montgomery, Douglas C.; Jennings, Cheryl L., author; Kulahci, Murat, author (Hoboken, New Jersey John Wiley & Sons, Inc., 2015)
Introduction to forecasting -- Statistics background for forecasting -- Regression analysis and forecasting -- Exponential smoothing methods -- Autoregressive integrated moving average (ARIMA) models -- Transfer functions and intervention models -- Survey of other forecasting methods -- Appendix A. Statistical tables -- Appendix B. Data sets for exercises
Contents: Introduction to Forecasting - - Statistics Background for Forecasting - - Regression Analysis and Forecasting - - Exponential Smoothing Methods - - Autoregressive Integrated Moving Average (ARIMA) Models - - Transfer Functions and Intervention Models - - Survey of Other Forecasting Methods.
Includes bibliographical references (pages 437-441) and index.
Keywords: Time-series analysis; Forecasting